Purification of Crude Glycerol Using Regenerated Spent Bleaching Earth as Palm Oil Refinery Process - Wahyuni, Sry; Rizka Fadhillah, Dinda (KOVALEN: Jurnal Riset Kimia, 2025)
Spent Bleaching Earth (SBE) is a type of solid waste generated during the palm oil refining process. Several studies have investigated the potential reuse of SBE as a valuable material, particularly as an adsorbent in glycerol purification. Crude glycerol, a by-product of biodiesel and oleochemical production from palm oil, is typically of low quality and contains numerous impurities, including free fatty acids (FFA) and pigmented compounds such as beta carotene and chlorophyll. In this study, SBE was regenerated using various solvents and subsequently calcined at 500 oC for 2 hours. Its surface was further modified with cetyltrimethylammonium bromide (CTAB) to enhance its adsorption capacity. The results showed that SBE regenerated with n-hexane and subjected to calcination exhibited the highest removal efficiency for beta carotene and chlorophyll. Further analysis of the physical and chemical properties of crude glycerol purified using uncalcined, calcined, and CTAB-modified SBE demonstrated that the modified SBE delivered the best adsorbent performance. The purified glycerol using modified SBE had the following characteristics: Moisture content (10.3%), Density (1.25 g/cm3), Free fatty acid (FFA) content (1.2%), Salt content (4.6%), beta-carotene content (0.843 ppm), Chlorophyll content (0.11 ppm) and pH approximately 6.